Enhancing Open and Distance Learning Materials: Validating the AFCI Model for Basic Chemistry - Jamaludin Jamaludin; Bachriah Fatwa Dhini; Faizal Akhmad Adi Masbukhin; Al Hafid; Paken Pandiangan (Postgraduate, University of Mataram, 2023)
In this study, we present the validation of the AFCI (Analysis and Identification, Find Color, Color Composition, and Implementation) model as a problem-based approach to enhance the quality of multicolor output in open and distance learning materials. The primary objective was to evaluate the reliability and validity of the AFCI model, specifically designed to incorporate two-color separation techniques aimed at reducing costs while improving the quality of multicolor content. Our research encompassed the examination of printed modules and samples across diverse subject areas, including Basic Chemistry, Architecture, Enterprise System Design, and Teacher Profession. To establish the validity of the AFCI model, a comprehensive validation process was conducted, involving focused group discussions with experts specializing in graphic design, printing, and educational materials. The outcomes of this rigorous validation process revealed substantial validity coefficients (rÎ± visibility = 0.98, rÎ± attractiveness = 0.97, rÎ± convenience = 0.91, rÎ± emphasis = 1), affirming the model's effectiveness. Furthermore, the internal consistency of the AFCI model was confirmed with a Cronbach's Alpha coefficient of 0.86. This research significantly contributes to the realm of open and distance learning by introducing an innovative model for improving multicolor content quality. The AFCI model's successful validation underscores its potential to benefit practitioners and educators in developing high-quality teaching materials, thereby enhancing the overall learning experience in open and distance education.